Crossing the minefield : tactics for overcoming today's toughest management challenges - Barner, Robert (AMACOM, 1994)
Crossing the Minefield is a front-line guide to surviving the daily bombardment of pressures and problems that managers must endure in an era of constant change. Robert W. Barner has distilled the problems to six basic challenges: (1) how to respond quickly to demands from both senior management and customers; (2) how to manage stress and burnout in yourself and your team members; (3) how to focus efforts on truly critical issues; (4) how to motivate your work team and yourself to the highest performance possible; (5) how to make the most of available staff; and (6) how to use positive politics to forge alliances with other managers and departments.